Prevalence and predictors of gastroesophageal reflux disease in pregnant women and its effects on quality of life and pregnancy outcomes - Dong Seok Lee; Ji Won Kim; Kook Lae Lee; Byeong Gwan Kim (Journal of Gynecological Research and Obstetrics - Peertechz Publications, 2021)
Introduction: Pregnancy is considered a risk factor for Gastroesophageal Reflux (GERD). However, studies on GERD during pregnancy are rare in Korea. We aimed to evaluate the efficacy and clinical outcomes of GERD in late pregnancy in Korea. Methods: Data from a total of 94 pregnant women in the second or third trimester at the SMG-SNU Boramae Medical Center for prenatal testing were analyzed in this study. The GERD questionnaire and Quality of Life in Reflux and Dyspepsia questionnaire were used to diagnose GERD and Quality of Life (QoL). Obstetric delivery records were utilized for pregnancy outcomes. Results: Approximately 30 percent (30%) of pregnant women had GERD. The incidence of GERD during pregnancy was higher in pregnant women with a history of GERD (p=0.041) or low Body Mass Index (BMI) (p=0.036). However, the incidence of GERD during pregnancy did not increase in proportion to the weight gain. QoL was significantly different between pregnant women with and without GERD: emotional stress (p=0.014), sleep problems (p=0.015), food/drink problems (p=0.004), and vitality (p=0.029). There was no significant difference in pregnancy outcomes between the two groups.  Conclusion: This study shows that pregnant women with GERD and low BMI tend to present with GERD symptoms during pregnancy. GERD adversely affects the QoL of pregnant women.